A study of the catechol amine content of red blood cells and plasma in hemorrhagic and hypoglycemic shock - Zileli, M. Şeref (The Turkish Journal of Pediatrics, 1959)
This study was performed on 5 dogs. Two animals received one unit of crystalline insulin per kilo of body weight. The other three dogs were bled to shock. The total catechol amine output of the adrenal gland was determined by analyzing the adrenal vein blood plasma and red blood cells separately. The findings showed that hypoglycemia or hemorrhagic shock in dogs is accompanied by the appearance of large quantities of catechol amines in the adrenal vein blood plasma. On the other hand, the catechol amine content of the red blood cells dropped significantly at the time of stress. It is suggested that the low catechol amine content of the red blood cells under experimental conditions is due to rapid destruction by the cell.